2014
DOI: 10.1111/trf.12895
|View full text |Cite
|
Sign up to set email alerts
|

Whole blood treated with riboflavin and ultraviolet light: quality assessment of all blood components produced by the buffy coat method

Abstract: Treatment of WB with riboflavin and UV before production of components by the BC method shows a negative impact on all three blood components. PLT units produced from PI-treated WB exhibited less damage compared to PLT component treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
47
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 38 publications
14
47
0
4
Order By: Relevance
“…Therefore, it is not surprising to detect platelet activation after Mirasol treatment. Similar patterns of reduced in vitro PC quality (including platelet degranulation as response to ADP) after Mirasol treatment have been well documented .…”
Section: Discussionsupporting
confidence: 62%
“…Therefore, it is not surprising to detect platelet activation after Mirasol treatment. Similar patterns of reduced in vitro PC quality (including platelet degranulation as response to ADP) after Mirasol treatment have been well documented .…”
Section: Discussionsupporting
confidence: 62%
“…To assess the suitability of the UVB/riboflavin treatment for whole blood, the viability of the different components was tested in vitro. Schubert et al found significant deterioration in plasma coagulation factor activation and increased RBC aging in components derived from whole blood that was PI-treated [144]. Interestingly, platelets showed fewer lesions than PI-treated PCs.…”
Section: The Overlap Of Redox Proteomics and Transfusionmentioning
confidence: 99%
“…Moreover, if IBS treatment induces discrete protein modifications such as rupture of hydrogen or ionic bonds, these modifications will not be detected on a 2D gel, although they could have a dramatic impact on the function of the protein. To access less abundant proteins, another possibility would be to combine the 2D‐DIGE method with differential off‐gel proteomic approaches like isobaric tagging for relative and absolute quantification (iTRAQ), stable isotope–labeled amino acids, or isotope‐coded affinity tags, which are all based on a differential analysis of labeled peptides and hence are more sensitive than a differential protein analysis …”
Section: Discussionmentioning
confidence: 99%